The Relationship between Folic Acid Intake and Depression among College Students - Persada, Tashila Zahra; Puspitasari, Dyah Intan (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
The aim of this study was to investigate the relationship between folic acid intake and the incidence of depression among students of Universitas Muhammadiyah Surakarta, department of Nutrition. This cross-sectional study recruited 40 participants following the inclusion criteria. Sample collection was done by random sampling. Data collection on the adequacy of folic acid intake was carried out using the non-consecutive three days 24 four Food recall. The prevalence of depression was obtained by measuring the level of depression in the last two weeks using the Beck Depression Inventory-II (BDI-II) questionnaire. The results showed that 2.5% of the subjects had sufficient folic acid intake and 97.5% had insufficient folic acid intake with mean 78,5 mcg. About 47.5% of subjects experienced minimal depression, 20% experienced mild depression, 25% experienced moderate depression, and 7.5% experienced major depression with mean score 13.4. Futher analysis, the p-value (p=0.145) indicated that there was no significant relationship between folic acid and depression status. Recommended for using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) to see acid intake folate and pay attention to other factors that cause depression.